Predictors of leptomeningeal disease following hypofractionated stereotactic radiotherapy for intact and resected brain metastases. Issue 1 (15th August 2019) - Nguyen, Timothy K; Sahgal, Arjun; Detsky, Jay; Atenafu, Eshetu G; Myrehaug, Sten; Tseng, Chia-Lin; Husain, Zain; Heyn, Chris; Maralani, Pejman; Ruschin, Mark; Perry, James; Soliman, Hany
Abstract: Background: The objective was to evaluate the risk and predictors of developing leptomeningeal disease (LMD) in patients with brain metastases treated with 5-fraction hypofractionated stereotactic radiotherapy (HSRT). Methods: Patients treated with HSRT for intact brain metastases and/or surgical cavities were reviewed from a prospectively maintained database. Radiographic patterns of LMD were classified as focal classical, diffuse classical, focal nodular, and diffuse nodular. Results: HSRT was delivered, most commonly 30 Gy in 5 fractions, to 320 intracranial lesions (57% intact and 43% surgical cavities) in 235 patients. The median follow-up was 13.4 months (range, 0.8 to 60 mo). LMD developed in 19% of patients with a 1-year LMD rate of 12%. From the diagnosis of LMD, the median overall survival (OS) was 3.8 months (range, 2–20.8 mo). The most common LMD pattern was diffuse nodular (44%). No difference in OS was observed between LMD patterns ( P = 0.203). Multivariable analysis identified surgical cavities at significantly higher risk of LMD compared with intact lesions (odds ratio [OR] = 2.30, 95% CI: 1.24, 4.29, P = 0.008). For cavities, radiosensitive tumors (OR = 2.35, 95% CI: 1.04, 5.35, P = 0.041) predicted for LMD, while, for intact metastases, patients receiving treatment with targeted agents or immunotherapy (TA/I) were at lower risk (OR = 0.178, 95% CI: 0.04, 0.79, P = 0.023). Conclusions: Patients who had a brain metastasis resected were at an increased risk of LMD. OS was poor despite treatment of LMD, and no differences in OS based on the pattern of LMD was observed. Treatment with TA/I was observed to be protective against LMD and requires further study.